New auxetic materials with stretch-dominant architecture using simple trusses. Issue 3 (1st February 2023) - Jafari Nedoushan, Reza; An, Yongsan; Yu, Woong-Ryeol
Abstract: Cellular auxetic materials, as a group of metamaterials, have received much interest due to their promising mechanical properties in various applications. The main shortcomings of cellular auxetic materials are their low stiffness and strength, due to a bending-dominant architecture. Here, a novel concept to design auxetic stretch-dominated structures is presented. Three example structures are analyzed in detail, to demonstrate the tunability and extensive range of positive and negative Poisson's ratio for these structures. Results show that the relative stiffnesses of the three test structures are several times higher than those of previously reported auxetic structures, for example, reentrant models.